PENGARUH ETOS KERJA, PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA GURU YPP SABILAL MUHTADIN BALIKPAPAN - jurnalpps pps; Madinatul Munawarah; Woro Utari; Indra Prasetyo (Jurnal Manajerial Bisnis, 2022)
This study aims to determine the effect of work ethic, education and work experience on the work productivity of YPP Sabilal Muhtadin Balikpapan teachers. This type of research is research with quantitative methods. The research sample was all teachers, totaling 42 respondents. The results showed that the teacher's work ethic had a significant effect on the work productivity of YPP YPP Sabilal Muhtadin Balikpapan teachers. Education has a significant effect on the work productivity of YPP YPP teachers Sabilal Muhtadin Balikpapan. Work experience has a significant effect on the work productivity of YPP YPP teacher Sabilal Muhtadin Balikpapan. Simultaneously work ethic, education and work experience have a significant effect on the work productivity of YPP Sabilal Muhtadin Balikpapan teachers.